Dust suppressant and preparation method thereof

By using dust inhibitor technology that combines polyacrylic resin with water, the existing dust inhibitors have been solved, and the problems of slow consolidation rate and low bonding strength under low temperature conditions are achieved, and rapid bonding, high strength and durability are achieved. The cured layer effectively suppresses the dust in coal, fine powder ore and other bulk materials.

CN119432325APending Publication Date: 2025-02-14METALS & CHEM RES INST CHINA ACAD OF RAILWAY SCI +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411536447.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing dust inhibitors have slow consolidation rate under low temperature conditions, low bonding strength, and are susceptible to factors such as vibration and water volatility, causing the cured layer to fail, so they cannot quickly and effectively suppress dust.

Method used

Polyacrylic resin is used as the film forming substance and water is used as a solvent to form a cured layer with high bond strength with coal, fine powder ore and other bulk materials, thereby enhancing the water resistance, drying resistance and wind corrosion resistance of dust inhibitors .

Benefits of technology

It realizes fast bonding and high-strength cured layer, has good durability and dust suppression effect, and can effectively prevent dust and environmental pollution in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005111666880000161
    Figure BDA0005111666880000161
  • Figure BDA0005111666880000171
    Figure BDA0005111666880000171
  • Figure BDA0005111666880000172
    Figure BDA0005111666880000172
Patent Text Reader

Abstract

The invention provides a dust suppressant and a preparation method thereof, and the dust suppressant comprises the following components in parts by mass: polyacrylic resin, a corrosion inhibitor, an auxiliary agent and water. The dust suppressant disclosed by the invention is environment-friendly, excellent in adhesive property, dust suppression property, corrosion resistance and durability, and capable of effectively reducing flying dust and coal loss. And meanwhile, the dust suppression requirements of bulk materials such as coal and fine mineral aggregates in the railway and highway transportation and stacking process can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental protection, and particularly relates to a dust suppressant and a preparation method thereof. Background Art

[0002] my country is rich in resources such as coal and ore. However, bulk materials such as coal and fine powdered ore are prone to dust problems during mining, transportation, and storage, which leads to pollution of the surrounding air, soil, and water. To date, a variety of solutions have been developed at home and abroad to address the dust problems that are prone to occur with bulk materials such as coal and fine powdered ore, including mechanical covering, tarpaulin covering, container trucks, and spraying water and dust suppressants. Among them, the dust suppression methods using mechanical covering, tarpaulin covering, and container trucks have problems such as high cost, difficulty in implementation, and impact on transportation efficiency. Compared with the above methods, spraying dust suppressants is a low-cost and easy-to-implement dust prevention method.

[0003] At present, the commonly used dust suppressants mainly include inorganic salts, organic matter and biomass, etc. They are used in the transportation and stacking of bulk materials such as coal and fine powder minerals in my country, and the quality of suppressing coal dust has been improved. Since the adhesive components in the dust suppressant solution need to be volatilized by water, and can only be bonded with the particles of bulk materials such as coal and fine powder minerals to form a solidified layer after reaching a certain aggregation concentration, they are highly dependent on the consolidation temperature and consolidation time. However, the consolidation rate is slow under low temperature conditions (especially in winter), and thus cannot play a rapid dust suppression role. In addition, even if the dust suppressant used on site has formed a solidified layer on the surface of bulk materials such as coal and fine powder minerals, due to its low bonding strength, it is also easily affected by vibration and water volatilization during transportation, resulting in powdering and cracking, and failure under the effects of drying, wind erosion, rain erosion, etc.

[0004] Therefore, it is of great practical significance to develop new dust suppressants with fast adhesion, high strength and strong durability. Summary of the invention

[0005] In order to overcome the deficiencies of the prior art, the present invention provides a dust suppressant and a preparation method thereof. The dust suppressant uses polyacrylic acid resin as a film-forming substance and water as a solvent, has good adhesion to particles of bulk materials such as coal and fine powdered minerals, can be quickly bonded, and has high strength after bonding. At the same time, the dust suppressant has good water resistance, drying resistance, and wind erosion resistance, so it has good durability and can be used to prevent the loss and environmental pollution of bulk materials such as coal and fine powdered minerals during railway and road transportation and stacking.

[0006] The present invention adopts the following technical solution:

[0007] In one aspect, the present invention provides a dust suppressant, which comprises, by weight, a polyacrylic resin, a corrosion inhibitor, an additive and water.

[0008] Preferably, the dust suppressant comprises, by weight, 0.5-5 parts of polyacrylic resin, 0.01-1 parts of corrosion inhibitor, 0.05-1 parts of auxiliary agent and 95-100 parts of water.

[0009] Preferably, the dust suppressant comprises, by weight, 1-5 parts of polyacrylic resin, 0.02-0.6 parts of corrosion inhibitor, 0.05-1 parts of auxiliary agent and 95-100 parts of water.

[0010] Preferably, the dust suppressant further comprises an inorganic or organic base and / or a thickener.

[0011] Preferably, the dust suppressant comprises, by weight, 0.5-5 parts of polyacrylic resin, 0.01-1 parts of corrosion inhibitor, 0.05-1 parts of auxiliary agent, 95-100 parts of water, 0-2 parts of inorganic or organic base and / or 0-1 parts of thickener.

[0012] Preferably, the dust suppressant comprises, by weight, 1-5 parts of polyacrylic resin, 0.02-0.6 parts of corrosion inhibitor, 0.05-1 parts of auxiliary agent, 95-100 parts of water, 0-1 parts of inorganic or organic base and / or 0-0.6 parts of thickener.

[0013] Preferably, the dust suppressant comprises, by weight, 1-5 parts of polyacrylic resin, 0.02-0.6 parts of corrosion inhibitor, 0.05-1 parts of auxiliary agent, 95-100 parts of water, 0.1-1 parts of inorganic or organic base and / or 0-0.6 parts of thickener.

[0014] Preferably, the polyacrylic resin is selected from one or more of polyacrylic acid, polyhydroxyethyl acrylate, polyhydroxypropyl acrylate, polymethacrylic acid, polyhydroxyethyl methacrylate, polyhydroxypropyl methacrylate, acrylic acid-hydroxyethyl acrylate copolymer, acrylic acid-hydroxypropyl acrylate copolymer, acrylic acid-hydroxyethyl methacrylate copolymer, acrylic acid-hydroxypropyl methacrylate copolymer, methacrylic acid-hydroxyethyl acrylate copolymer, methacrylic acid-hydroxypropyl acrylate copolymer, acrylic acid-methacrylic acid-hydroxyethyl methacrylate copolymer, acrylic acid-methacrylic acid-hydroxypropyl methacrylate copolymer and polyacrylates thereof, polymethacrylate, acrylate-hydroxyethyl acrylate copolymer, acrylate-hydroxypropyl acrylate copolymer, acrylate-hydroxyethyl methacrylate copolymer, acrylate-hydroxypropyl methacrylate copolymer, methacrylate-hydroxyethyl acrylate copolymer, methacrylate-hydroxypropyl acrylate copolymer, acrylate-methacrylic acid-hydroxypropyl methacrylate copolymer, acrylate-methacrylate-hydroxypropyl methacrylate copolymer and acrylate-methacrylate-hydroxypropyl methacrylate copolymer.

[0015] Preferably, the polyacrylic resin is selected from polyacrylic acid, polyhydroxyethyl acrylate, polyhydroxypropyl acrylate, polymethacrylic acid, polyhydroxyethyl methacrylate, polyhydroxypropyl methacrylate, acrylic acid-hydroxyethyl acrylate copolymer, acrylic acid-hydroxypropyl acrylate copolymer, acrylic acid-hydroxyethyl methacrylate copolymer, acrylic acid-hydroxypropyl methacrylate copolymer, methacrylic acid-hydroxyethyl acrylate copolymer, methacrylic acid-hydroxypropyl acrylate copolymer, acrylic acid-methacrylic acid-hydroxyethyl methacrylate copolymer, acrylic acid-methacrylic acid-hydroxypropyl methacrylate copolymer and polyacrylic acid (sodium, magnesium, calcium, zinc), polymethacrylic acid (sodium, magnesium, calcium, zinc)-hydroxyethyl acrylate copolymer, acrylic acid (sodium, magnesium, calcium, zinc)-hydroxypropyl acrylate copolymer One or more of the following: acrylic acid (sodium, magnesium, calcium, zinc)-hydroxyethyl methacrylate copolymer, acrylic acid (sodium, magnesium, calcium, zinc)-hydroxypropyl methacrylate copolymer, methacrylic acid (sodium, magnesium, calcium, zinc)-hydroxyethyl acrylate copolymer, methacrylic acid (sodium, magnesium, calcium, zinc)-hydroxypropyl acrylate copolymer, acrylic acid-methacrylic acid (sodium, magnesium, calcium, zinc)-hydroxyethyl methacrylate copolymer, acrylic acid (sodium, magnesium, calcium, zinc)-methacrylic acid-hydroxyethyl methacrylate copolymer, acrylic acid (sodium, magnesium, calcium, zinc)-methacrylic acid-hydroxypropyl methacrylate copolymer, acrylic acid-methacrylic acid (sodium, magnesium, calcium, zinc)-hydroxypropyl methacrylate copolymer, acrylic acid (sodium, magnesium, calcium, zinc)-methacrylic acid (sodium, magnesium, calcium, zinc)-hydroxypropyl methacrylate copolymer.

[0016] The polyacrylic acid resin used in the present invention can be synthesized chemically or purchased commercially.

[0017] Preferably, the weight average molecular weight of the polyacrylic acid resin is 1,000-600,000.

[0018] More preferably, the weight average molecular weight of the polyacrylic acid resin is 1,000-300,000.

[0019] Preferably, the inorganic or organic base is selected from one or more of sodium hydroxide, calcium oxide, calcium hydroxide, potassium hydroxide, triethylamine, ethanolamine, triethanolamine and diethanolamine.

[0020] More preferably, the inorganic or organic base is selected from one or more of sodium hydroxide, calcium hydroxide, ethanolamine, triethanolamine and diethanolamine.

[0021] Preferably, the corrosion inhibitor is selected from one or more of citrate, nitrite, silicate, molybdate, benzotriazole and its derivatives, benzothiazole and its derivatives, imidazoline and its derivatives, imidazole and its derivatives.

[0022] More preferably, the corrosion inhibitor is selected from one or more of silicates, benzotriazole and its derivatives, benzothiazole and its derivatives, imidazoline and its derivatives, imidazole and its derivatives.

[0023] Preferably, the thickener is selected from one or more of polyvinyl alcohol, polyethylene glycol, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, sodium hydroxycellulose, sodium carboxymethyl cellulose, and polyacrylamide.

[0024] More preferably, the thickener is selected from one or more of polyvinyl alcohol, hydroxyethyl cellulose, hydroxypropyl cellulose, sodium hydroxycellulose, sodium carboxymethyl cellulose, and polyacrylamide.

[0025] Preferably, the auxiliary agent is selected from one or more of a wetting agent, an emulsifier and a surfactant. The auxiliary agent of the present invention can be selected from commercially available products commonly used in the art, including Triton X-100, AEO-9, OP-10 and OP-21.

[0026] On the other hand, the present invention provides a method for preparing the above-mentioned dust suppressant, which comprises adding polyacrylic acid resin and water into a dispersion kettle and stirring, then sequentially adding inorganic or organic base, corrosion inhibitor, thickener, and auxiliary agent, stirring and mixing for 10-20 minutes to obtain the dust suppressant.

[0027] In this application, the mass fractions of each component represent the mass ratio relationship between the components. According to actual conditions, the preparation of dust suppressant can be any mass number, such as 1g, 5g, 10g, 50g, 250g, 500g, 1kg, 1 ton, 10 tons, etc.

[0028] The dust suppressant of the present invention is composed of a combination of polyacrylic acid high molecular polymers. Functional groups such as carboxyl and hydroxyl groups in the polymer interact with each other through hydrogen bonds, and a cross-linked network structure is formed between molecules. As the polymer concentration increases, the cross-linking degree of the polymer network structure is further increased, and the bonding strength is further improved. At the same time, there are various ion groups between molecules. Due to the large charge density, a strong affinity is generated between the molecules and the particles of dust can be quickly captured and firmly adsorbed through coagulation, adhesion and other effects. After drying, it can be solidified with the dust particles into a shell film, so it has a strong dust suppression and dust prevention effect.

[0029] The dust suppressant of the present invention combines a polyacrylic acid polymer with corrosion inhibitors such as citrate, nitrite, silicate, molybdate, benzotriazole and its derivatives, benzothiazole and its derivatives, imidazoline and its derivatives, imidazole and its derivatives, to obtain a new dust suppressant with rapid adhesion, high strength, strong durability and corrosion resistance.

[0030] When the dust suppressant of the present invention is used for the transportation and stacking of bulk materials such as coal and fine powder minerals, it is easy to form a flexible chain network structure with multiple hydrogen bonds and a certain proportion, so that it can quickly bond with the particles of bulk materials such as coal and fine powder minerals and maintain a high-strength bonding force, and can resist strong wind erosion and avoid serious dust. In addition to the rapid bonding, high bonding strength and dust suppression effects, the dust suppressant of the present invention also has the effects of "external waterproofing, internal moisturizing and reversible bonding" when formed with the solidified layer of bulk material particles such as coal and fine powder minerals. The solidified layer only softens and the bonding strength decreases when eroded by rainwater. As the surface moisture content decreases, its bonding strength can gradually increase.

[0031] The dust suppressant of the present invention has the effect of "external waterproofing and internal moisturizing". After being used in low humidity environments such as sunlight exposure and drying, the dust suppression solidified layer formed is not prone to weathering, powdering and cracking. Therefore, the dust suppressant of the present invention can not only reduce dust during the transportation and stacking of coal and mineral powder particles, but also cope with complex environments such as wind erosion, rain erosion and drying, and has excellent dust suppression and durability effect, reducing the number of times the dust suppressant needs to be sprayed, thereby achieving cost reduction and efficiency improvement, and significant environmental and social benefits. DETAILED DESCRIPTION

[0032] The present invention is described below with reference to specific examples. It will be appreciated by those skilled in the art that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention in any way.

[0033] The experimental methods in the following examples are conventional methods unless otherwise specified. The raw materials, reagents, etc. used in the following examples are commercially available products unless otherwise specified. The purchase of some raw materials is as follows:

[0034] Polyacrylic acid, polymethacrylic acid, polyhydroxyethyl acrylate, polyhydroxypropyl acrylate, acrylic acid-hydroxyethyl acrylate copolymer, acrylic acid-hydroxyethyl methacrylate copolymer, acrylic acid-methacrylic acid-hydroxyethyl methacrylate copolymer, acrylic acid-methacrylic acid-hydroxyethyl acrylate copolymer, calcium polyacrylate, polyhydroxyethyl methacrylate, calcium polymethacrylate, magnesium polyacrylate, polyhydroxyethyl methacrylate, calcium acrylate-methacrylic acid-hydroxyethyl acrylate copolymer: Nanjing Zhenzhi New Material Technology Co., Ltd.;

[0035] Polyvinyl alcohol, hydroxyethyl cellulose, hydroxypropyl cellulose, sodium hydroxycellulose, sodium carboxymethyl cellulose, polyacrylamide: Beijing Qianmen Chemical Co., Ltd.;

[0036] Triethanolamine, diethanolamine: Shanghai MacLean Biochemical Technology Co., Ltd.;

[0037] Triton X-100, AEO-9, OP-10 and OP-21: Beijing Qianmen Chemical Co., Ltd.

[0038] Example 1

[0039] First, add polyacrylic acid (20 kg) and water (980 kg) into a dispersion kettle and stir, then add polyvinyl alcohol (5 kg), triethanolamine (1 kg), imidazoline corrosion inhibitor (0.1 kg), OP-10 emulsifier (0.5 kg) in sequence, and stir and mix the raw materials for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0040] Example 2

[0041] First, add polyhydroxyethyl acrylate (20 kg) and water (980 kg) into a dispersion kettle and stir, then add polyvinyl alcohol (5 kg), triethanolamine (1 kg), imidazoline corrosion inhibitor (0.1 kg), OP-10 emulsifier (0.5 kg) in sequence, and stir and mix the raw materials for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0042] Example 3

[0043] First, add polyhydroxypropyl acrylate (20 kg) and water (980 kg) into a dispersion kettle and stir, then add polyvinyl alcohol (5 kg), triethanolamine (1 kg), imidazoline corrosion inhibitor (0.1 kg), OP-10 emulsifier (0.5 kg) in sequence, and stir and mix the raw materials for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0044] Example 4

[0045] First, acrylic acid-hydroxyethyl acrylate copolymer (20 kg) and water (980 kg) are added to a dispersion kettle and stirred, and then polyvinyl alcohol (5 kg), triethanolamine (1 kg), imidazoline corrosion inhibitor (0.1 kg), OP-21 emulsifier (0.5 kg) are added in sequence. After each component raw material is stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0046] Example 5

[0047] First, acrylic acid-hydroxyethyl methacrylate copolymer (20 kg) and water (980 kg) are added to a dispersion kettle and stirred, and then polyvinyl alcohol (5 kg), triethanolamine (1 kg), imidazoline corrosion inhibitor (0.1 kg), OP-21 emulsifier (0.5 kg) are added in sequence, and each component raw material is stirred and mixed for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0048] Example 6

[0049] First, acrylic acid-methacrylic acid-hydroxyethyl methacrylate copolymer (20 kg) and water (980 kg) are added to a dispersion kettle and stirred, and then polyvinyl alcohol (5 kg), triethanolamine (1 kg), imidazoline corrosion inhibitor (0.1 kg), OP-21 emulsifier (0.5 kg) are added in sequence, and each component raw material is stirred and mixed for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0050] Example 7

[0051] First, acrylic acid-methacrylic acid-hydroxyethyl acrylate copolymer (20 kg) and water (980 kg) are added to a dispersion kettle and stirred, and then polyvinyl alcohol (5 kg), triethanolamine (1 kg), imidazoline corrosion inhibitor (0.1 kg), OP-21 emulsifier (0.5 kg) are added in sequence, and each component raw material is stirred and mixed for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0052] Example 8

[0053] First, acrylic acid-methacrylic acid-hydroxyethyl acrylate copolymer (50 kg) and water (1000 kg) are added to a dispersion kettle and stirred, and then polyvinyl alcohol (5 kg), triethanolamine (10 kg), imidazoline corrosion inhibitor (1 kg), OP-21 emulsifier (1 kg) are added in sequence, and each component raw material is stirred and mixed for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0054] Example 9

[0055] First, acrylic acid-methacrylic acid-hydroxyethyl acrylate copolymer (5 kg) and water (950 kg) are added to a dispersion kettle and stirred, and then polyvinyl alcohol (10 kg), triethanolamine (1 kg), imidazoline corrosion inhibitor (0.1 kg), OP-21 emulsifier (0.5 kg) are added in sequence, and each component raw material is stirred and mixed for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0056] Example 10

[0057] First, polyacrylic acid (1 kg), acrylic acid-hydroxyethyl acrylate copolymer (4 kg) and water (950 kg) are added to a dispersion kettle and stirred, and then triethanolamine (1 kg), imidazoline corrosion inhibitor (0.1 kg), polyvinyl alcohol (10 kg), OP-21 emulsifier (0.5 kg) are added in sequence. After the raw materials of each component are stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0058] Embodiment 11

[0059] First, polyacrylic acid (1 kg), acrylic acid-hydroxyethyl methacrylate copolymer (4 kg) and water (950 kg) are added to a dispersion kettle and stirred, and then triethanolamine (1 kg), imidazoline corrosion inhibitor (0.1 kg), hydroxyethyl cellulose (10 kg), OP-21 emulsifier (0.5 kg) are added in sequence. After each component raw material is stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0060] Example 12

[0061] First, polymethacrylic acid (1 kg), acrylic acid-hydroxyethyl methacrylate copolymer (4 kg) and water (950 kg) are added to a dispersion kettle and stirred, and then triethanolamine (1 kg), imidazoline corrosion inhibitor (0.1 kg), hydroxyethyl cellulose (10 kg), OP-21 emulsifier (0.5 kg) are added in sequence. After each component raw material is stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0062] Embodiment 13

[0063] First, polyacrylic acid (1 kg), polymethacrylic acid (1 kg), acrylic acid-hydroxyethyl acrylate copolymer (3 kg) and water (950 kg) are added to a dispersion kettle and stirred, and then triethanolamine (1 kg), imidazoline corrosion inhibitor (0.1 kg), hydroxyethyl cellulose (10 kg), OP-21 emulsifier (0.5 kg) are added in sequence. After the raw materials of each component are stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0064] Embodiment 14

[0065] First, polyacrylic acid (1 kg), polymethacrylic acid (1 kg), acrylic acid-hydroxypropyl acrylate copolymer (3 kg) and water (950 kg) are added to a dispersion kettle and stirred, and then triethanolamine (1 kg), imidazoline corrosion inhibitor (0.1 kg), hydroxyethyl cellulose (5 kg), OP-21 emulsifier (0.5 kg) are added in sequence. After each component raw material is stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0066] Embodiment 15

[0067] First, polyacrylic acid (5 kg), acrylic acid-hydroxyethyl acrylate copolymer (5 kg), sodium polyacrylate (5 kg) and water (980 kg) are added to a dispersion kettle and stirred, and then imidazoline corrosion inhibitor (0.1 kg), polyvinyl alcohol (5 kg), OP-10 emulsifier (0.5 kg) are added in sequence. After each component raw material is stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0068] Example 16

[0069] First, polyacrylic acid (5 kg), acrylic acid-hydroxyethyl acrylate copolymer (5 kg), magnesium polyacrylate (5 kg) and water (980 kg) are added to a dispersion kettle and stirred, and then imidazoline corrosion inhibitor (0.1 kg), hydroxyethyl cellulose (5 kg), AEO-9 (0.5 kg) are added in sequence. After each component raw material is stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0070] Embodiment 17

[0071] First, polyacrylic acid (5 kg), acrylic acid-hydroxyethyl acrylate copolymer (5 kg), calcium polyacrylate (5 kg) and water (980 kg) are added to a dispersion kettle and stirred, and then imidazoline corrosion inhibitor (0.1 kg), hydroxypropyl cellulose (5 kg), and Triton X-100 (1.0 kg) are added in sequence. After each component raw material is stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0072] Embodiment 18

[0073] First, add polyacrylic acid (5 kg), polyhydroxyethyl acrylate (5 kg), sodium polyacrylate (5 kg) and water (980 kg) into a dispersion kettle and stir, then add imidazoline corrosion inhibitor (0.1 kg), polyacrylamide (5 kg), OP-21 emulsifier (0.5 kg) in sequence, and stir and mix the raw materials for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0074] Embodiment 19

[0075] First, polymethacrylic acid (5 kg), polyhydroxyethyl acrylate (5 kg), magnesium polyacrylate (5 kg) and water (980 kg) are added to a dispersion kettle and stirred, and then benzotriazole corrosion inhibitor (0.1 kg), polyacrylamide (5 kg), OP-21 emulsifier (1.0 kg) are added in sequence. After each component raw material is stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0076] Embodiment 20

[0077] First, add polyhydroxyethyl acrylate (25 kg), calcium polyacrylate (5 kg) and water (965 kg) into a dispersion kettle and stir, then add benzothiazole corrosion inhibitor (0.1 kg), hydroxymethyl cellulose (5 kg), OP-21 emulsifier (0.5 kg) in sequence, and stir and mix the raw materials for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0078] Embodiment 21

[0079] First, add polyacrylic acid (2 kg), polyhydroxyethyl acrylate (7 kg), zinc polyacrylate (1 kg) and water (975 kg) into a dispersion kettle and stir, then add imidazole corrosion inhibitor (0.1 kg), hydroxyethyl cellulose (5 kg), OP-21 emulsifier (0.5 kg) in sequence, and stir and mix the raw materials for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0080] Embodiment 22

[0081] First, add polyacrylic acid (2 kg), polyhydroxyethyl methacrylate (7 kg), calcium polyacrylate (1 kg) and water (970 kg) into a dispersion kettle and stir, then add borax corrosion inhibitor (0.1 kg), hydroxyethyl cellulose (5 kg), OP-21 emulsifier (0.5 kg) in sequence, and stir and mix the raw materials for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0082] Embodiment 23

[0083] First, polymethacrylic acid (2 kg), polyhydroxyethyl acrylate (10 kg), calcium polymethacrylate (3 kg) and water (980 kg) are added to a dispersion kettle and stirred, and then imidazoline corrosion inhibitor (0.1 kg), polyvinyl alcohol (5 kg), OP-21 emulsifier (0.5 kg) are added in sequence. After each component raw material is stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0084] Embodiment 24

[0085] First, polymethacrylic acid (5 kg), polyhydroxyethyl acrylate (10 kg), calcium polyacrylate (10 kg) and water (975 kg) are added to a dispersion kettle and stirred, and then imidazoline corrosion inhibitor (0.2 kg), polyvinyl alcohol (2 kg), OP-21 emulsifier (0.5 kg) are added in sequence. After each component raw material is stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0086] Embodiment 25

[0087] First, add polyacrylic acid (5 kg), polyhydroxyethyl acrylate (15 kg), calcium polyacrylate (5 kg) and water (975 kg) into a dispersion kettle and stir, then add triethanolamine (1 kg), imidazoline corrosion inhibitor (0.1 kg), polyvinyl alcohol (5 kg), OP-21 emulsifier (0.5 kg) in sequence, and stir and mix the raw materials for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0088] Embodiment 26

[0089] First, polyacrylic acid (5 kg), polyhydroxyethyl acrylate (25 kg), calcium polyacrylate (5 kg) and water (965 kg) are added to a dispersion kettle and stirred, and then imidazoline corrosion inhibitor (0.1 kg), polyvinyl alcohol (5 kg), Triton X-100 (0.1 kg), OP-21 emulsifier (0.2 kg) are added in sequence, and each component raw material is stirred and mixed for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0090] Embodiment 27

[0091] First, polymethacrylic acid (5 kg), polyhydroxyethyl acrylate (25 kg), magnesium polyacrylate (5 kg) and water (960 kg) are added to a dispersion kettle and stirred, and then imidazoline corrosion inhibitor (0.2 kg), hydroxyethyl cellulose (5 kg), OP-21 emulsifier (0.5 kg) are added in sequence. After each component raw material is stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0092] Embodiment 28

[0093] First, polyacrylic acid (5 kg), polyhydroxypropyl acrylate (16 kg), calcium polyacrylate (4 kg) and water (975 kg) are added to a dispersion kettle and stirred, and then triethanolamine (1 kg), imidazoline corrosion inhibitor (0.1 kg), hydroxypropyl cellulose (5 kg), Triton X-100 (0.1 kg), OP-21 emulsifier (0.1 kg) are added in sequence, and each component raw material is stirred and mixed for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0094] Embodiment 29

[0095] First, polyacrylic acid (10 kg), polyhydroxyethyl methacrylate (10 kg), calcium polyacrylate (5 kg) and water (965 kg) are added to a dispersion kettle and stirred, and then triethanolamine (1 kg), imidazoline corrosion inhibitor (0.2 kg), polyacrylamide (5 kg), Triton X-100 (0.5 kg), OP-21 emulsifier (0.5 kg) are added in sequence, and each component raw material is stirred and mixed for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0096] Embodiment 30

[0097] First, polyacrylic acid (10 kg), polyhydroxyethyl acrylate (10 kg) and water (980 kg) are added to a dispersion kettle and stirred, and then diethanolamine (1 kg), imidazole corrosion inhibitor (0.2 kg), hydroxyethyl cellulose (2 kg), Triton X-100 (0.2 kg), OP-21 emulsifier (0.3 kg) are added in sequence, and each component raw material is stirred and mixed for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0098] Embodiment 31

[0099] First, polyacrylic acid (10 kg), polyhydroxypropyl acrylate (10 kg) and water (980 kg) are added to a dispersion kettle and stirred, and then diethanolamine (1 kg), benzotriazole corrosion inhibitor (0.2 kg), polyacrylamide (2 kg), Triton X-100 (0.2 kg), OP-21 emulsifier (0.3 kg) are added in sequence, and each component raw material is stirred and mixed for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0100] Embodiment 32

[0101] First, polyacrylic acid (10 kg), polyhydroxyethyl methacrylate (10 kg) and water (980 kg) are added to a dispersion kettle and stirred, and then diethanolamine (1 kg), benzothiazole corrosion inhibitor (0.2 kg), polyacrylamide (2 kg), Triton X-100 (0.2 kg), OP-21 emulsifier (0.3 kg) are added in sequence, and each component raw material is stirred and mixed for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0102] Embodiment 33

[0103] First, polymethacrylic acid (10 kg), polyhydroxyethyl acrylate (10 kg) and water (980 kg) are added to a dispersion kettle and stirred, and then diethanolamine (1 kg), imidazoline corrosion inhibitor (0.2 kg), hydroxyethyl cellulose (5 kg), Triton X-100 (0.2 kg), OP-21 emulsifier (0.3 kg) are added in sequence, and each component raw material is stirred and mixed for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0104] Embodiment 34

[0105] First, polymethacrylic acid (30 kg), polyhydroxyethyl methacrylate (20 kg) and water (950 kg) are added to a dispersion kettle and stirred, and then triethanolamine (1 kg), imidazoline corrosion inhibitor (1 kg), and polyacrylamide (2 kg) are added in sequence. After each component raw material is stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0106] Embodiment 35

[0107] First, add polyacrylic acid (25 kg), polyhydroxyethyl acrylate (20 kg), calcium polyacrylate (5 kg) and water (950 kg) into a dispersion kettle and stir, then add triethanolamine (1 kg), imidazoline corrosion inhibitor (1 kg), hydroxyethyl cellulose (2 kg) in sequence, and stir and mix the raw materials for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0108] Embodiment 36

[0109] First, polyacrylic acid (5 kg), acrylic acid-hydroxyethyl acrylate copolymer (20 kg), polyhydroxyethyl acrylate (10 kg) and water (965 kg) are added to a dispersion kettle and stirred, and then triethanolamine (1 kg), imidazoline corrosion inhibitor (0.5 kg), hydroxyethyl cellulose (2 kg) are added in sequence. After the raw materials of each component are stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0110] Embodiment 37

[0111] First, polyacrylic acid (1 kg), acrylic acid-hydroxyethyl acrylate copolymer (2 kg), polyhydroxyethyl acrylate (2 kg) and water (985 kg) are added to a dispersion kettle and stirred, and then imidazoline corrosion inhibitor (0.5 kg) and hydroxyethyl cellulose (10 kg) are added in sequence. After the raw materials of each component are stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0112] Embodiment 38

[0113] First, polyacrylic acid (1 kg), acrylic acid-hydroxyethyl acrylate copolymer (2 kg), calcium polyacrylate (2 kg) and water (985 kg) are added to a dispersion kettle and stirred, and then imidazoline corrosion inhibitor (0.5 kg) and hydroxyethyl cellulose (10 kg) are added in sequence. After each component raw material is stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0114] Embodiment 39

[0115] First, polyacrylic acid (1 kg), acrylic acid-hydroxyethyl acrylate copolymer (2 kg), calcium polyacrylate (2 kg) and water (985 kg) are added to a dispersion kettle and stirred, and then imidazoline corrosion inhibitor (0.5 kg) and hydroxyethyl cellulose (10 kg) are added in sequence. After each component raw material is stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0116] Embodiment 40

[0117] First, polyacrylic acid (1 kg), acrylic acid-methacrylic acid-hydroxyethyl acrylate copolymer (2 kg), calcium acrylate-methacrylic acid-hydroxyethyl acrylate copolymer (2 kg) and water (975 kg) are added to a dispersion kettle and stirred, and then triethanolamine (1 kg), imidazoline corrosion inhibitor (0.1 kg), polyvinyl alcohol (5 kg), OP-21 emulsifier (0.5 kg) are added in sequence. After the raw materials of each component are stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0118] Comparative Example 1

[0119] First, hydroxyethyl cellulose (10 kg) and water (990 kg) are added to a dispersion kettle and stirred, and then imidazoline corrosion inhibitor (0.5 kg) is added. After the raw materials of each component are stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0120] Comparative Example 2

[0121] First, polyethylene glycol (10 kg) and water (990 kg) are added to a dispersion kettle and stirred, and then imidazoline corrosion inhibitor (0.5 kg) is added. After the raw materials of each component are stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0122] Comparative Example 3

[0123] First, polyvinyl alcohol (10 kg) and water (990 kg) are added to a dispersion kettle and stirred, and then imidazoline corrosion inhibitor (0.5 kg) is added. After the raw materials of each component are stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0124] Comparative Example 4

[0125] First, polyvinyl alcohol (20 kg) and water (980 kg) are added to a dispersion kettle and stirred, and then imidazoline corrosion inhibitor (0.5 kg) and sodium carboxymethyl cellulose (5 kg) are added in sequence. After each component raw material is stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0126] Comparative Example 5

[0127] First, add polyacrylic acid (1 kg), acrylic acid-hydroxyethyl acrylate copolymer (1 kg), polyacrylic acid resin hydroxyethyl ester (1 kg) and water (1000 kg) into a dispersion kettle and stir, then add imidazoline corrosion inhibitor (0.2 kg), hydroxyethyl cellulose (3 kg), OP-21 emulsifier (0.3 kg), stir and mix the raw materials for 10-20 minutes to obtain a dust suppressant. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0128] Comparative Example 6

[0129] First, polyacrylic acid (5 kg), acrylic acid-hydroxyethyl acrylate copolymer (10 kg), polyhydroxyethyl acrylate (5 kg) and water (980 kg) were added to a dispersion kettle and stirred, and then hydroxyethyl cellulose (3 kg) and OP-21 emulsifier (0.3 kg) were added. After the raw materials of each component were stirred and mixed for 10-20 minutes, a dust suppressant was obtained. The dust suppressant solution was stored in a cool and ventilated place for standby use.

[0130] Comparative Example 7

[0131] First, polymethacrylic acid (5 kg), methacrylic acid-hydroxyethyl methacrylate copolymer (10 kg), calcium polyacrylate (5 kg) and water (980 kg) were added to a dispersion kettle and stirred, and then hydroxyethyl cellulose (3 kg) and OP-21 emulsifier (0.3 kg) were added. After the raw materials of each component were stirred and mixed for 10-20 minutes, a dust suppressant was obtained. The dust suppressant solution was stored in a cool and ventilated place for standby use.

[0132] Comparative Example 8

[0133] First, sodium polyacrylate (10 kg), calcium polyacrylate (10 kg) and water (980 kg) are added to a dispersion kettle and stirred, and then hydroxyethyl cellulose (3 kg) and OP-21 emulsifier (0.3 kg) are added. After the raw materials of each component are stirred and mixed for 10-20 minutes, a dust suppressant is obtained. The dust suppressant solution is stored in a cool and ventilated place for standby use.

[0134] Test example: Performance measurement of coal dust suppressants of Examples 1-40 and Comparative Examples 1-8

[0135] This test example tests the metal corrosion, wind erosion rate under high wind speed, and compressive strength of the solidified layer of the coal dust suppressants of Examples 1-40 and Comparative Examples 1-8.

[0136] (1) Metal Corrosion

[0137] The test is carried out according to the method specified in JB / T7901. The test piece is placed in a glass sealed container containing dust suppressant solution and immersed for 168 hours at an ambient temperature of (20±5)℃. The arithmetic mean of 3 test samples for each material is taken as the test result.

[0138] (2) Wind erosion rate at high wind speed

[0139] The test method refers to TB / T 3210.1-2020 "Technical Conditions for Dust Suppression in Railway Coal Transportation Part 1: Dust Suppressants". The test samples were cured for 2h and 4h at 0℃ and room temperature (23±2℃), respectively. The wind speed of the wind erosion test was 45m / s. The samples were weighed before and after the erosion test to obtain the mass loss of coal after erosion.

[0140] Wind erosion rate calculation formula: R = (m1-m2) / (m1-m0)

[0141] Where R——wind erosion rate (%)

[0142] m0——empty tray weight (g)

[0143] m1——Total weight of coal, dust suppressant and empty tray before blowing (g)

[0144] m2——Total weight of coal, dust suppressant and empty tray after erosion (g)

[0145] (3) Compressive strength of the cured layer

[0146] The sample preparation method refers to TB / T 3210.1-2020 "Technical Conditions for Dust Suppression in Railway Coal Transportation Part 1: Dust Suppressants". The test samples were cured for 2h and 4h at 0℃ and room temperature (23±2℃), and watered for 4h and dried for 72h. The compressive strength was measured by thrust gauge (Note: The contact area of ​​the dynamometer used in this patent is 28mm 2 ) was tested, and at least 6 points were selected at different positions of the sample to test its average maximum destructive force, and the compressive strength was calculated according to the following formula.

[0147] Compressive strength calculation formula: P = F / S

[0148] Where P——compressive strength (N / mm 2 or MPa)

[0149] F——average maximum breaking force of the solidified layer (N)

[0150] S——Dynamometer contact area (mm 2 ).

[0151] (4) Test results

[0152] The main performance test results of the dust suppressants of Examples 1-40 and Comparative Examples 1-7 are shown in Table 1 and Table 2, respectively.

[0153] Table 1 Performance test results of dust suppressants of Examples 1-40

[0154]

[0155]

[0156] Table 2 Performance test results of dust suppressants of comparative examples 1-8

[0157]

[0158]

[0159] According to the above test results, it can be seen that the main properties of the dust suppressants in Examples 1-40 all meet the requirements; while the wind erosion rates of the dust suppressants in Comparative Examples 1-5 and 8, and the Q450NQR1 metal corrosion properties of the dust suppressants in Comparative Examples 5, 6, and 7 do not meet the standard requirements, and the other test items of the dust suppressants in Comparative Examples 1-8 all meet the requirements.

[0160] The above measurement results show that the dust suppressant provided by the present invention has excellent bonding and dust suppression performance. The wind erosion rate of the solidified layer formed by the dust suppressant after solidification at room temperature (23±2°C) is less than 1.0; at the same time, the dust suppressant of the present invention is suitable for use at different temperatures. The higher the temperature, the faster the solidification and the higher the bonding strength. The strength test value of the solidified layer at room temperature (23±2°C) and 0°C is 0.1-0.8MPa, and the solidified layer can still remain intact and have bonding strength after being sprinkled with water and dried. In short, the dust suppressant of the present invention can meet the dust suppression requirements of bulk materials such as coal and fine powder minerals during railway and road transportation and stacking. At the same time, the dust suppressant has strong durability in complex environments of wind erosion, rain erosion and drying.

Claims

1. A dust suppressant, which comprises, by weight, a polyacrylic resin, a corrosion inhibitor, an additive and water.

2. The dust suppressant according to claim 1, wherein The dust suppressant comprises, by weight, 0.5-5 parts of polyacrylic acid resin, 0.01-1 parts of corrosion inhibitor, 0.05-1 parts of auxiliary agent and 95-100 parts of water; Preferably, the dust suppressant comprises, by weight, 1-5 parts of polyacrylic resin, 0.02-0.6 parts of corrosion inhibitor, 0.05-1 parts of auxiliary agent and 95-100 parts of water.

3. The dust suppressant according to claim 1 or 2, wherein: The dust suppressant also includes an inorganic or organic base and / or a thickener; Preferably, the dust suppressant comprises, by weight, 0.5-5 parts of polyacrylic resin, 0.01-1 parts of corrosion inhibitor, 0.05-1 parts of auxiliary agent, 95-100 parts of water, 0-2 parts of inorganic or organic base and / or 0-1 parts of thickener; Preferably, the dust suppressant comprises, by weight, 1-5 parts of polyacrylic resin, 0.02-0.6 parts of corrosion inhibitor, 0.05-1 parts of auxiliary agent, 95-100 parts of water, 0-1 parts of inorganic or organic base and / or 0-0.6 parts of thickener; Preferably, the dust suppressant comprises, by weight, 1-5 parts of polyacrylic resin, 0.02-0.6 parts of corrosion inhibitor, 0.05-1 parts of auxiliary agent, 95-100 parts of water, 0.1-1 parts of inorganic or organic base and / or 0-0.6 parts of thickener.

4. The dust suppressant according to any one of claims 1 to 3, wherein The polyacrylic resin is selected from one or more of polyacrylic acid, polyhydroxyethyl acrylate, polyhydroxypropyl acrylate, polymethacrylic acid, polyhydroxyethyl methacrylate, polyhydroxypropyl methacrylate, acrylic acid-hydroxyethyl acrylate copolymer, acrylic acid-hydroxypropyl acrylate copolymer, acrylic acid-hydroxyethyl methacrylate copolymer, acrylic acid-hydroxypropyl methacrylate copolymer, methacrylic acid-hydroxyethyl acrylate copolymer, methacrylic acid-hydroxypropyl acrylate copolymer, acrylic acid-methacrylic acid-hydroxyethyl methacrylate copolymer, acrylic acid-methacrylic acid-hydroxypropyl methacrylate copolymer and polyacrylates thereof, polymethacrylate, acrylate-hydroxyethyl acrylate copolymer, acrylate-hydroxypropyl acrylate copolymer, acrylate-hydroxyethyl methacrylate copolymer, acrylate-hydroxypropyl methacrylate copolymer, methacrylate-hydroxyethyl acrylate copolymer, methacrylate-hydroxypropyl acrylate copolymer, acrylate-methacrylic acid-hydroxypropyl methacrylate copolymer, acrylate-methacrylate-hydroxypropyl methacrylate copolymer; Preferably, the polyacrylic resin is selected from polyacrylic acid, polyhydroxyethyl acrylate, polyhydroxypropyl acrylate, polymethacrylic acid, polyhydroxyethyl methacrylate, polyhydroxypropyl methacrylate, acrylic acid-hydroxyethyl acrylate copolymer, acrylic acid-hydroxypropyl acrylate copolymer, acrylic acid-hydroxyethyl methacrylate copolymer, acrylic acid-hydroxypropyl methacrylate copolymer, methacrylic acid-hydroxyethyl acrylate copolymer, methacrylic acid-hydroxypropyl acrylate copolymer, acrylic acid-methacrylic acid-hydroxyethyl methacrylate copolymer, acrylic acid-methacrylic acid-hydroxypropyl methacrylate copolymer and polyacrylic acid (sodium, magnesium, calcium, zinc), polymethacrylic acid (sodium, magnesium, calcium, zinc)-hydroxyethyl acrylate copolymer, acrylic acid (sodium, magnesium, calcium, zinc)-hydroxypropyl acrylate copolymer One or more of the following: acrylic acid (sodium, magnesium, calcium, zinc)-hydroxyethyl methacrylate copolymer, acrylic acid (sodium, magnesium, calcium, zinc)-hydroxypropyl methacrylate copolymer, methacrylic acid (sodium, magnesium, calcium, zinc)-hydroxyethyl acrylate copolymer, methacrylic acid (sodium, magnesium, calcium, zinc)-hydroxypropyl acrylate copolymer, acrylic acid-methacrylic acid (sodium, magnesium, calcium, zinc)-hydroxyethyl methacrylate copolymer, acrylic acid (sodium, magnesium, calcium, zinc)-methacrylic acid-hydroxyethyl methacrylate copolymer, acrylic acid (sodium, magnesium, calcium, zinc)-methacrylic acid-hydroxypropyl methacrylate copolymer, acrylic acid-methacrylic acid (sodium, magnesium, calcium, zinc)-hydroxypropyl methacrylate copolymer, acrylic acid (sodium, magnesium, calcium, zinc)-methacrylic acid (sodium, magnesium, calcium, zinc)-hydroxypropyl methacrylate copolymer.

5. The dust suppressant according to any one of claims 1 to 4, wherein The weight average molecular weight of the polyacrylic acid resin is 1000-600000; More preferably, the weight average molecular weight of the polyacrylic acid resin is 1,000-300,000.

6. The dust suppressant according to any one of claims 1 to 5, wherein The inorganic or organic base is selected from one or more of sodium hydroxide, calcium oxide, calcium hydroxide, potassium hydroxide, triethylamine, ethanolamine, triethanolamine and diethanolamine; More preferably, the inorganic or organic base is selected from one or more of sodium hydroxide, calcium hydroxide, ethanolamine, triethanolamine and diethanolamine.

7. The dust suppressant according to any one of claims 1 to 6, wherein The corrosion inhibitor is selected from one or more of citrate, nitrite, silicate, molybdate, benzotriazole and its derivatives, benzothiazole and its derivatives, imidazoline and its derivatives, imidazole and its derivatives; More preferably, the corrosion inhibitor is selected from one or more of silicates, benzotriazole and its derivatives, benzothiazole and its derivatives, imidazoline and its derivatives, imidazole and its derivatives.

8. The dust suppressant according to any one of claims 1 to 7, wherein The thickener is selected from one or more of polyvinyl alcohol, polyethylene glycol, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, sodium hydroxycellulose, sodium carboxymethyl cellulose, and polyacrylamide; More preferably, the thickener is selected from one or more of polyvinyl alcohol, hydroxyethyl cellulose, hydroxypropyl cellulose, sodium hydroxycellulose, sodium carboxymethyl cellulose, and polyacrylamide.

9. The dust suppressant according to any one of claims 1 to 8, wherein The auxiliary agent is selected from one or more of a wetting agent, an emulsifier and a surfactant; Preferably, the auxiliary agent is selected from one or more of Triton X-100, AEO-9, OP-10 and OP-21.

10. A method for preparing the dust suppressant according to any one of claims 1 to 9, comprising adding polyacrylic acid resin and water into a dispersion kettle and stirring, then sequentially adding an inorganic or organic base, a corrosion inhibitor, a thickener, and an auxiliary agent, and stirring and mixing for 10-20 minutes to obtain the dust suppressant.